On the Structure and Source of Individual Differences in Toddlers' Comprehension of Transitive Sentences - Donnelly, Seamus; Kidd, Evan (Frontiers in Psychology, 2021)
How children learn grammar is one of the most fundamental questions in cognitive science. Two theoretical accounts--Early Abstraction and Usage-Based accounts--have been proposed to answer this question. To compare predictions of these accounts, we tested 92 twenty-four month olds’ comprehension of transitive sentences with novel verbs (e.g., “The boy is gorping the girl!” using the Intermodal Preferential Looking Task (IMPL). We found very little evidence that children looked to the target video at above-chance levels, suggesting that our sample had not yet acquired a fully abstract representation of transitive sentence structure. Using mixed and mixture models, we tested predictions the two accounts make about: (i) the structure of individual differences on the IMPL task, and (ii) the relationship between vocabulary knowledge, lexical processing, and performance on the IMPL task. However, results did not strongly support either of the two accounts. Implications for theories of language acquisition, and for tasks developed for examining individual differences are discussed.